DEVELOPING ANDROID-BASED HISTORYTOON MEDIA FOR HISTORY LEARNING - Septia Rahandinasari (Universitas Negeri Yogyakarta, 2018)
ABSTRACTIn the present era, advances in technology and communication are growing rapidly, especially in the field of education, it is necessary to develop learning media based on information and communication technology. The development of instructional media must be in accordance with the purpose of learning, but it is also the learning media that can make the students are educated to be independent in accordance with the teacher's direction. This study aims to develop historical learning media as an online comic reading service. Currently researchers are using Historytoon to create a formative involving high school students in Yogyakarta. Based on the testing of the learning media, it can produce a decent historical learning media and can improve the understanding of the material of the National Movement of Indonesia class XI SMA. Keywords: Historytoon media, Android, History Learning